The Use of Medical Foods to Fight Chronic Diseases: A Narrative Review - Aslihan Demirdöven; Hilal Meral (Journal of Agricultural Sciences)
Chronic diseases cannot be treated completely, and, therefore, often require repeated treatments. This issue leads to long-term drug utilization. However, medical foods can offer alternative natural drugs in the management and treatment of chronic diseases. Medical foods are specially formulated food to meet the particular nutritional requirements of patients affected by certain diseases. They play an important role in nutritional support for patients in clinical applications such as deglutition, dyspepsia or eating disorders. Moreover, they considerably enhance the quality of living of patients by reducing drug usage, preventing complications that may arise through the overreliance of drugs, and reducing the expenses of treatments. The nutritive value of medical foods can be regulated and personalized depending on the disease. Since they are not drugs, they exempt from regulations applying to drugs. Each medical food is formulated specifically for the relevant chronic disease. However, there are no studies in the literature that provide examples of medical foods for different diseases available in the market. The examination and compilation of medical foods, including examples from the market, is vital both in terms of creating new products and filling the gap in the relevant literature. Consequently, the aim of this review is to explain the use of medical foods for Alzheimer’s, Parkinson’s, anxiety and sleep disorder, pain syndrome, cancer, congenital metabolic disorders, diabetes mellitus, and indicate why should be used as a nutritional supplement for these chronic diseases.